Frequency Characteristics of Pulse Wave Sensor Using MEMS Piezoresistive Cantilever Element - Taiga Nabeshima; Thanh-Vinh Nguyen; Hidetoshi Takahashi (Micromachines, 2022)
Wearable sensor devices with minimal discomfort to the wearer have been widely developed to realize continuous measurements of vital signs (body temperature, blood pressure, respiration rate, and pulse wave) in many applications across various fields, such as healthcare and sports. Among them, microelectromechanical systems (MEMS)-based differential pressure sensors have garnered attention as a tool for measuring pulse waves with weak skin tightening. Using a MEMS-based piezoresistive cantilever with an air chamber as the pressure change sensor enables highly sensitive pulse-wave measurements to be achieved. Furthermore, the initial static pressure when attaching the sensor to the skin is physically excluded because of air leakage around the cantilever, which serves as a high-pass filter. However, if the frequency characteristics of this mechanical high-pass filter are not appropriately designed, then the essential information of the pulse-wave measurement may not be reflected. In this study, the frequency characteristics of a sensor structure is derived theoretically based on the air leakage rate and chamber size. Subsequently, a pulse wave sensor with a MEMS piezoresistive cantilever element, two air chambers, and a skin-contacted membrane is designed and fabricated. The developed sensor is 30 mm in diameter and 8 mm in thickness and realizes high-pass filter characteristics of 0.7 Hz. Finally, pulse wave measurement at the neck of a participant is demonstrated using the developed sensor. It is confirmed that the measured pulse wave contains signals in the designed frequency band.